2000
DOI: 10.1128/cmr.13.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Classification, Identification, and Clinical Significance ofProteus,Providencia, andMorganella

Abstract: SUMMARY This review presents the current taxonomy of the genera Proteus, Providencia, and Morganella, along with the current methods for the identification of each species within the three genera, incorporating both conventional biochemical and commercial methods. While all of these organisms are ubiquitous in the environment, individual case reports and nosocomial outbreak reports that demonstrate their ability to cause major infectious disease problems are presented. Lastly, anticipated ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
248
3
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(266 citation statements)
references
References 102 publications
8
248
3
7
Order By: Relevance
“…The phylogenetic tree showed that the strain NSPH-1 16S rRNA sequences had a high similarity with the other sequences of P. hauseri. Proteus is pathogenic bacteria, causing ulcers, in different fishes (Mandal et al, 2002) and UTI in humans (O'Hara et al, 2000b). Pathogenicity tests suggested that the NSPH-1 caused haemorrhages in the tail fin and mortality of the fish in the experimental infection.…”
Section: Tablementioning
confidence: 99%
“…The phylogenetic tree showed that the strain NSPH-1 16S rRNA sequences had a high similarity with the other sequences of P. hauseri. Proteus is pathogenic bacteria, causing ulcers, in different fishes (Mandal et al, 2002) and UTI in humans (O'Hara et al, 2000b). Pathogenicity tests suggested that the NSPH-1 caused haemorrhages in the tail fin and mortality of the fish in the experimental infection.…”
Section: Tablementioning
confidence: 99%
“…It is found in the environment and in the intestinal tracts of humans, mammals, and reptiles as part of the normal flora. Despite its wide distribution, it is an uncommon cause of infections in humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…15 Aeromonas and Morganella are both facultative anaerobic gram-negative motile bacilli. 16,17 Aeromonas along with Vibrio species are associated with rapid onset of cellulitis and clinically severe disease, requiring aggressive debridement and culture-directed antimicrobial therapy. 18 The attack rate of the organism after exposure can be greater than 40%.…”
Section: Discussionmentioning
confidence: 99%